Automated planning of children's stories using causal links, agents and commonsense ontology - Ong, Ethel Chua Joy (Philippine computing journal)
Building computer systems that have the ability to generate human understandable stories has been the subject of research in the field of the computational narrative, as these can find applications in education and entertainment...